2014
DOI: 10.1103/physrevb.89.094514
|View full text |Cite
|
Sign up to set email alerts
|

Role of the 245 phase in alkaline iron selenide superconductors revealed by high-pressure studies

Abstract: There is considerable interest in uncovering the physics of iron-based superconductivity from the alkaline iron selenides, a materials class containing an insulating phase (245 phase) and a superconducting (SC) phase. Due to the microstructural complexity of these superconductors, the role of the 245 phase in the development of the superconductivity has been a puzzle. Here we demonstrate a comprehensive high-pressure study on the insulating samples with pure 245 phase and biphasic SC samples. We find that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…The commonly observed 245 phase exists in all the nominal compositions of Rb 0.8 Fe 2 Se 2−z S z as a mesoscopically separated phase. Note that the Fe content is in fact less than 2 which means that all of the samples are in the two phase coexistence region [11][12][13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Rb08fe2s2mentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly observed 245 phase exists in all the nominal compositions of Rb 0.8 Fe 2 Se 2−z S z as a mesoscopically separated phase. Note that the Fe content is in fact less than 2 which means that all of the samples are in the two phase coexistence region [11][12][13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Rb08fe2s2mentioning
confidence: 99%
“…1 (x ≈ 0.8, y ≈ 1.6, referred to as the 245 phase) always seems to be mesoscopically interdigitated with the SC phase that has been suggested to be an iron vacancy free phase in the studies to-date [10][11][12][13][14][15][16][17][18][19][20][21][22][23] . The relationships between the two phases are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…This phase has been observed around 100-300 K in the multi-band metallic phase by angle resolved photoemission spectroscopy (ARPES) [26]. In addition, a recent high pressure study [27] has underlined the importance of the OSMP phase as an intermediate phase between the iron-vacancy ordered insulating texture and the minority metallic phase. Also a recent high energy x-ray emission (XES) study has found anomalous evolution of the magnetic phase below 300 K that can arXiv:1501.06745v1 [cond-mat.supr-con] 27 Jan 2015 be assigned to the OSMP phase [28].…”
Section: Introductionmentioning
confidence: 96%
“…The OSMP phase arises in multiorbital Hubbard models of the FeSCs, which contain both Hubbard interactions and Hund's coupling 11,12 . Evidence for the OSMP has also come from a variety of other measurements [13][14][15][16] . A complementary approach to the electron correlations of the FeSCs describes the localization-delocalization phenomena in the form of an orbital differentiation and a coherence-incoherence crossover 17,18 , though OSMP is not explicitly invoked.…”
Section: Introductionmentioning
confidence: 99%